A lithium iron phosphate material, preparation method and application thereof

Through the improved ball milling treatment of iron phosphate combined with graphene modified agent in lithium iron phosphate materials, thermal efficiency improvement treatment and secondary efficiency improvement of synergists, combined with sintering improvement treatment, the problem of coordinated improvement of specific capacity and conductivity performance of the material under high magnification and high circulation conditions is solved, and the high temperature resistance and stability are significantly improved and the product usage efficiency is improved.

CN119461307BActive Publication Date: 2025-03-28GANZHOU CYCLEWELL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510030957.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-28
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing lithium iron phosphate materials have poor specific capacity performance under high magnification and high cycle conditions, and the conductivity performance is difficult to coordinate and improve with specific capacity, and the high temperature resistance is insufficient, which limits the efficiency of the product.

Method used

The improved treatment of iron phosphate combined with graphene-adjusted ball mill is adopted, and the thermal efficiency improvement treatment is carried out and the secondary efficiency improvement of the synergist is improved. Finally, the sintering improvement treatment is carried out. The obtained lithium iron phosphate material is coordinated to improve the specific capacity and conductivity performance under high magnification and high circulation conditions, and significantly improves the high temperature stability.

Benefits of technology

Under high magnification and high circulation conditions, the specific capacity and conductivity performance of lithium iron phosphate materials have been coordinated and improved, and the product's high temperature resistance and stability have also been significantly improved, improving the product's use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461307B_ABST
    Figure CN119461307B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium iron phosphate materials, and in particular to a lithium iron phosphate material, a preparation method and an application thereof, comprising the following steps: 2 / g iron phosphate and graphene modifier are ball-milled in a weight ratio of 5: (2-3) for primary treatment, and after ball milling, filtered and dried to obtain graphene modified iron phosphate. The lithium iron phosphate material of the present invention adopts iron phosphate and graphene modifier for ball milling improvement treatment, and then undergoes thermal efficiency improvement treatment, and secondary synergistic improvement by synergist, and finally sintered to obtain the lithium iron phosphate material, which has coordinated improvement in specific capacity performance and conductivity performance under high rate and high cycle conditions, and the product has excellent high temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium iron phosphate materials, and in particular to a lithium iron phosphate material, a preparation method and application thereof. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in power tools, electric vehicles and energy storage due to their advantages such as high voltage platform, high energy density, no memory effect and long cycle life. Lithium iron phosphate material, as the positive electrode material of lithium-ion batteries, has excellent safety and cycle performance and is environmentally friendly, and is considered to be a highly promising power lithium-ion battery material.

[0003] The existing lithium iron phosphate materials have poor specific capacity performance under high rate and high cycle conditions. At the same time, the product's conductivity performance is difficult to coordinate and improve with the specific capacity under high rate and cycle conditions, and the product's high temperature stability is poor, further limiting the product's efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a lithium iron phosphate material, a preparation method and application thereof, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing a lithium iron phosphate material, comprising the following steps:

[0007] Step 1: Set the specific surface area to 5-8m / g iron phosphate and graphene modification agent are subjected to primary ball milling treatment in a weight ratio of 5:(2-3), and after the ball milling is completed, the iron phosphate agent modified with graphene is obtained by suction filtration and drying;

[0008] Step 2: subjecting the graphene-modified iron phosphate agent to thermal efficiency improvement treatment, and after the treatment is completed, a thermally efficient iron phosphate body is obtained;

[0009] Step 3: Mix the thermally effective iron phosphate, lithium carbonate and synergist in a weight ratio of (5-7): (3-4): 2 and perform a secondary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain an improved lithium iron phosphate.

[0010] Step 4: The lithium iron phosphate improved body is sintered and improved, and the lithium iron phosphate material of the present invention is obtained after sintering.

[0011] Preferably, the ball milling speed of the primary ball milling treatment is 750-850 r / min, and the ball milling is performed for 2 hours; the ball milling speed of the secondary ball milling treatment is 1000-1500 r / min, and the ball milling is performed for 30-40 minutes.

[0012] Preferably, the specific operation steps of the thermal efficiency improvement treatment are:

[0013] First, heat treat at 210-220℃ for 30-40min, then heat to 400-420℃ at a rate of 2-5℃ / min, and continue heat treatment for 20min;

[0014] Finally, heat to 500-530℃ at a rate of 1-3℃ / min, keep warm for 1h, and finally air cool to room temperature;

[0015] The operation steps of the sintering improvement treatment are:

[0016] Heat treat at 750-760℃ for 30-40min, then heat to 820-850℃ at a rate of 1-3℃ / min, keep warm for 2-3h, and finally air cool to room temperature.

[0017] Preferably, the preparation method of the graphene modifying agent is:

[0018] S01: The graphene is first ultrasonically treated in a sufficient amount of hydrogen peroxide solution, with an ultrasonic power of 350-400W for 20 minutes. After the ultrasonic treatment is completed, the graphene is washed with water, filtered and dried;

[0019] S02: Preparation of modified solution doped with nano-titanium dioxide:

[0020] 1-3 parts of nano-silica sol and 2-4 parts of 5% by mass lanthanum chloride solution are added to 5-8 parts of sodium citrate solution, and then 2-4 parts of nano-titanium dioxide are added to fully blend to obtain a modified solution doped with nano-titanium dioxide;

[0021] S03: stirring and modifying the dried graphene and the modified solution doped with nano-titanium dioxide in a weight ratio of 3:7, and completing the modification to obtain a modified graphene agent;

[0022] S04: The modified graphene agent and the regulator are mixed in a weight ratio of 5:3 and ball-milled at a speed of 750-850 r / min for 2 h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain the graphene modified regulator.

[0023] Preferably, the mass fraction of the hydrogen peroxide solution is 3-6%; the mass fraction of the sodium citrate solution is 4-7%; the stirring speed of the stirring modification treatment is 450-500 r / min, and the stirring time is 30-40 min.

[0024] Preferably, the preparation method of the regulator is:

[0025] The nano-kaolin powder is first immersed in a zinc nitrate solution 3-5 times the total amount of the nano-kaolin, and the solution is stirred sufficiently at a speed of 550-750 r / min for 2 hours. After the immersion is completed, the solution is filtered and dried to obtain a zinc-doped kaolin agent;

[0026] The flaky nano-alumina, chitosan solution and sodium dodecylbenzene sulfonate are mixed in a weight ratio of 3:5:1 to prepare a flaky nano-alumina liquid;

[0027] Add 4-7 parts of zinc-doped kaolin agent and 1-2 parts of silane coupling agent KH550 to 5-8 parts of flaky nano-alumina liquid, mix and ball-mill for 2 hours at 550-750r / min. After the ball-milling is completed, filter and dry to obtain a regulator.

[0028] Preferably, the mass fraction of the zinc nitrate solution is 4-8%; the mass fraction of the chitosan solution is 3-5%.

[0029] Preferably, the preparation method of the synergist is:

[0030] S11: irradiating the carbon nanotubes in a proton irradiation box at a power of 350-400 W for 20-30 min to obtain irradiated carbon nanotubes;

[0031] S12: 2-5 parts by mass of 4% sodium alginate solution, 1-3 parts by mass of 5% yttrium nitrate solution, 3-5 parts by mass of hydroxyapatite and 1-2 parts by mass of carboxymethyl cellulose are mixed to obtain a hydroxyapatite solution;

[0032] The irradiated carbon nanotubes and hydroxyapatite liquid are stirred and modified in a weight ratio of 2:5, with a stirring speed of 650-700 r / min for 20-30 minutes. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a synergist.

[0033] The present invention also provides a lithium iron phosphate material prepared by a method for preparing a lithium iron phosphate material.

[0034] The present invention also provides an application of lithium iron phosphate material in positive electrode material of lithium electronic battery.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The lithium iron phosphate material of the present invention adopts iron phosphate and graphene modification agent ball milling improvement treatment, and then through thermal efficiency improvement treatment, and through secondary synergistic improvement of synergist, and finally sintering to obtain the lithium iron phosphate material with coordinated improvement of specific capacity performance and conductivity performance under high rate and high cycle conditions, and the product has excellent high temperature stability;

[0037] 2. The graphene modification agent is to treat the graphene with a hydrogen peroxide solution to optimize its activity performance, and then to improve and optimize it with a modified solution doped with nano-titanium dioxide. The modified solution doped with nano-titanium dioxide is blended with nano-silica sol, 5% by mass lanthanum chloride solution, sodium citrate solution and nano-titanium dioxide. The graphene is improved with the blended modified solution doped with nano-titanium dioxide, so that the graphene can better coordinate and enhance the effect with the regulator, thereby optimizing the product performance effect;

[0038] 3. The regulator adopts nano-kaolin, which is immersed and stirred in a zinc nitrate solution to obtain zinc-doped nano-kaolin, and the nano-kaolin with a flaky structure is improved by ball milling with a flaky nano-alumina liquid and a silane coupling agent. The flaky nano-alumina, chitosan solution and sodium dodecylbenzene sulfonate in the flaky nano-alumina liquid are blended and adjusted, so that the flaky structure of the flaky nano-alumina is combined with the nano-kaolin structure to enhance the performance stability of the system, and the specific raw materials in the regulator are combined to further improve the performance effect of the system;

[0039] 4. The synergist adopts carbon nanotubes through proton irradiation to optimize the activity of carbon nanotubes, and then improves the treatment through hydroxyapatite liquid. The sodium alginate solution, 5% yttrium nitrate solution by mass, hydroxyapatite and carboxymethyl cellulose in the hydroxyapatite liquid are fully blended to obtain hydroxyapatite liquid. Through the coordination and matching between the raw materials, the hydroxyapatite body with a point structure is matched with the carbon nanotubes with a high specific surface area, so that the synergist obtained is reinforced in the system, which can better coordinate and synergize with the graphene modification agent, so that the performance coordination and performance stability of the product are further improved;

[0040] 5. The present invention adopts a thermal efficiency improvement treatment, first heat treating at a temperature of 210-220°C for 30-40min, then heating to 400-420°C at a rate of 2-5°C / min, and continuing the heat treatment for 20min; finally heating to 500-530°C at a rate of 1-3°C / min, keeping warm for 1h, and finally air cooling to room temperature. Through continuous segmented heating treatment, thermal homogenization improvement, and graphene modification and adjustment to jointly optimize the performance effect of the system, and then through sintering improvement treatment, the performance of the product is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is an electron microscope image of the lithium iron phosphate material of the present invention. DETAILED DESCRIPTION

[0042] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] A method for preparing a lithium iron phosphate material according to the present embodiment comprises the following steps:

[0044] Step 1: Set the specific surface area to 5-8m / g iron phosphate and graphene modification agent are subjected to primary ball milling treatment in a weight ratio of 5:(2-3), and after the ball milling is completed, the iron phosphate agent modified with graphene is obtained by suction filtration and drying;

[0045] Step 2: subjecting the graphene-modified iron phosphate agent to thermal efficiency improvement treatment, and after the treatment is completed, a thermally efficient iron phosphate body is obtained;

[0046] Step 3: Mix the thermally effective iron phosphate, lithium carbonate and synergist in a weight ratio of (5-7): (3-4): 2 and perform a secondary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain an improved lithium iron phosphate.

[0047] Step 4: The lithium iron phosphate improved body is sintered and improved, and the lithium iron phosphate material of the present invention is obtained after sintering.

[0048] The ball milling speed of the primary ball milling treatment in this embodiment is 750-850 r / min, and the ball milling is 2 hours; the ball milling speed of the secondary ball milling treatment is 1000-1500 r / min, and the ball milling is 30-40 minutes.

[0049] The specific operation steps of the thermal efficiency improvement process of this embodiment are:

[0050] First, heat treat at 210-220℃ for 30-40min, then heat to 400-420℃ at a rate of 2-5℃ / min, and continue heat treatment for 20min;

[0051] Finally, heat to 500-530℃ at a rate of 1-3℃ / min, keep warm for 1h, and finally air cool to room temperature;

[0052] The operation steps of the sintering improvement treatment are:

[0053] Heat treat at 750-760℃ for 30-40min, then heat to 820-850℃ at a rate of 1-3℃ / min, keep warm for 2-3h, and finally air cool to room temperature.

[0054] The preparation method of the graphene modifying agent of this embodiment is:

[0055] S01: The graphene is first ultrasonically treated in a sufficient amount of hydrogen peroxide solution, with an ultrasonic power of 350-400W for 20 minutes. After the ultrasonic treatment is completed, the graphene is washed with water, filtered and dried;

[0056] S02: Preparation of modified solution doped with nano-titanium dioxide:

[0057] 1-3 parts of nano-silica sol and 2-4 parts of 5% by mass lanthanum chloride solution are added to 5-8 parts of sodium citrate solution, and then 2-4 parts of nano-titanium dioxide are added to fully blend to obtain a modified solution doped with nano-titanium dioxide;

[0058] S03: stirring and modifying the dried graphene and the modified solution doped with nano-titanium dioxide in a weight ratio of 3:7, and completing the modification to obtain a modified graphene agent;

[0059] S04: The modified graphene agent and the regulator are mixed in a weight ratio of 5:3 and ball-milled at a speed of 750-850 r / min for 2 h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain the graphene modified regulator.

[0060] The mass fraction of the hydrogen peroxide solution in this embodiment is 3-6%; the mass fraction of the sodium citrate solution is 4-7%; the stirring speed of the stirring modification treatment is 450r-500 / min, and the stirring time is 30-40min.

[0061] The preparation method of the regulator of this embodiment is:

[0062] The nano-kaolin powder is first immersed in a zinc nitrate solution 3-5 times the total amount of the nano-kaolin, and the solution is stirred sufficiently at a speed of 550-750 r / min for 2 hours. After the immersion is completed, the solution is filtered and dried to obtain a zinc-doped kaolin agent;

[0063] The flaky nano-alumina, chitosan solution and sodium dodecylbenzene sulfonate are mixed in a weight ratio of 3:5:1 to prepare a flaky nano-alumina liquid;

[0064] Add 4-7 parts of zinc-doped kaolin agent and 1-2 parts of silane coupling agent KH550 to 5-8 parts of flaky nano-alumina liquid, mix and ball-mill for 2 hours at 550-750r / min. After the ball-milling is completed, filter and dry to obtain a regulator.

[0065] The mass fraction of the zinc nitrate solution in this embodiment is 4-8%; the mass fraction of the chitosan solution is 3-5%.

[0066] The preparation method of the synergist of this embodiment is:

[0067] S11: irradiating the carbon nanotubes in a proton irradiation box at a power of 350-400 W for 20-30 min to obtain irradiated carbon nanotubes;

[0068] S12: 2-5 parts by mass of 4% sodium alginate solution, 1-3 parts by mass of 5% yttrium nitrate solution, 3-5 parts by mass of hydroxyapatite and 1-2 parts by mass of carboxymethyl cellulose are mixed to obtain a hydroxyapatite solution;

[0069] The irradiated carbon nanotubes and hydroxyapatite liquid are stirred and modified in a weight ratio of 2:5, with a stirring speed of 650-700 r / min for 20-30 minutes. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a synergist.

[0070] The lithium iron phosphate material is prepared by a method for preparing a lithium iron phosphate material in this embodiment.

[0071] The present embodiment provides an application of a lithium iron phosphate material in a positive electrode material of a lithium electronic battery.

[0072] Example 1

[0073] A method for preparing a lithium iron phosphate material according to the present embodiment comprises the following steps:

[0074] Step 1: Set the specific surface area to 5m / g iron phosphate and graphene modification agent are subjected to primary ball milling treatment in a weight ratio of 5:2, and after the ball milling is completed, the iron phosphate agent modified with graphene is obtained by suction filtration and drying;

[0075] Step 2: subjecting the graphene-modified iron phosphate agent to thermal efficiency improvement treatment, and after the treatment is completed, a thermally efficient iron phosphate body is obtained;

[0076] Step 3: Mix the thermally effective iron phosphate, lithium carbonate and synergist in a weight ratio of 5:3:2 and perform secondary ball milling. After the ball milling is completed, filter and dry to obtain the improved lithium iron phosphate.

[0077] Step 4: The lithium iron phosphate improved body is sintered and improved, and the lithium iron phosphate material of the present invention is obtained after sintering.

[0078] The ball milling speed of the primary ball milling treatment in this embodiment is 750 r / min, and the ball milling is 2 hours; the ball milling speed of the secondary ball milling treatment is 1000 r / min, and the ball milling is 30 minutes.

[0079] The specific operation steps of the thermal efficiency improvement process of this embodiment are:

[0080] First, heat treat at 210℃ for 30min, then increase the temperature to 400℃ at a rate of 2℃ / min and continue heat treatment for 20min;

[0081] Finally, the temperature was raised to 500°C at a rate of 1°C / min, kept at that temperature for 1h, and finally air-cooled to room temperature;

[0082] The operation steps of the sintering improvement treatment are:

[0083] Heat treatment was performed at 750°C for 30 min, then the temperature was increased to 820°C at a rate of 1°C / min, kept at this temperature for 2 h, and finally air-cooled to room temperature.

[0084] The preparation method of the graphene modifying agent of this embodiment is:

[0085] S01: The graphene is first ultrasonically treated in a sufficient amount of hydrogen peroxide solution, with an ultrasonic power of 350W for 20 minutes. After the ultrasonic treatment is completed, the graphene is washed with water, filtered and dried;

[0086] S02: Preparation of modified solution doped with nano-titanium dioxide:

[0087] One part of nano-silica sol and two parts of 5% by mass lanthanum chloride solution are added to five parts of sodium citrate solution, and then two parts of nano-titanium dioxide are added to mix well to obtain a modified solution doped with nano-titanium dioxide;

[0088] S03: stirring and modifying the dried graphene and the modified solution doped with nano-titanium dioxide in a weight ratio of 3:7, and completing the modification to obtain a modified graphene agent;

[0089] S04: The modified graphene agent and the regulator are mixed in a weight ratio of 5:3 and ball-milled at a speed of 750 r / min for 2 h. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain the graphene modified regulator.

[0090] The mass fraction of the hydrogen peroxide solution in this embodiment is 3%; the mass fraction of the sodium citrate solution is 4%; the stirring speed of the stirring modification treatment is 450 r / min, and the stirring time is 30 min.

[0091] The preparation method of the regulator of this embodiment is:

[0092] The nano-kaolin powder is first immersed in a zinc nitrate solution 3 times the total amount of the nano-kaolin, and the solution is stirred sufficiently at a speed of 550 r / min for 2 hours. After the immersion is completed, the solution is filtered and dried to obtain a zinc-doped kaolin agent;

[0093] The flaky nano-alumina, chitosan solution and sodium dodecylbenzene sulfonate are mixed in a weight ratio of 3:5:1 to prepare a flaky nano-alumina liquid;

[0094] Add 4 parts of zinc-doped kaolin agent and 1 part of silane coupling agent KH550 into 5 parts of flaky nano-alumina liquid, mix and ball-mill for 2 hours at 550 r / min. After the ball-milling is completed, filter and dry to obtain a regulator.

[0095] The mass fraction of the zinc nitrate solution in this embodiment is 4%; the mass fraction of the chitosan solution is 3%.

[0096] The preparation method of the synergist of this embodiment is:

[0097] S11: irradiating the carbon nanotubes in a proton irradiation box at a power of 350 W for 20 min to obtain irradiated carbon nanotubes;

[0098] S12: 2 parts of 4% by mass sodium alginate solution, 1 part of 5% by mass yttrium nitrate solution, 3 parts of hydroxyapatite and 1 part of carboxymethyl cellulose are mixed to obtain a hydroxyapatite solution;

[0099] The irradiated carbon nanotubes and hydroxyapatite liquid were stirred and modified in a weight ratio of 2:5, with a stirring speed of 650 r / min for 20 minutes. After the stirring was completed, the mixture was washed with water, filtered and dried to obtain a synergist.

[0100] The lithium iron phosphate material is prepared by a method for preparing a lithium iron phosphate material in this embodiment.

[0101] The present embodiment provides an application of a lithium iron phosphate material in a positive electrode material of a lithium electronic battery.

[0102] Example 2

[0103] A method for preparing a lithium iron phosphate material according to the present embodiment comprises the following steps:

[0104] Step 1: Set the specific surface area to 8m / g iron phosphate and graphene modification agent are subjected to primary ball milling treatment in a weight ratio of 5:3, and after the ball milling is completed, the iron phosphate agent modified with graphene is obtained by suction filtration and drying;

[0105] Step 2: subjecting the graphene-modified iron phosphate agent to thermal efficiency improvement treatment, and after the treatment is completed, a thermally efficient iron phosphate body is obtained;

[0106] Step 3: The thermally effective iron phosphate, lithium carbonate and synergist are mixed in a weight ratio of 7:4:2 and subjected to secondary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain an improved lithium iron phosphate.

[0107] Step 4: The lithium iron phosphate improved body is sintered and improved, and the lithium iron phosphate material of the present invention is obtained after sintering.

[0108] The ball milling speed of the first-level ball milling treatment in this embodiment is 850 r / min, and the ball milling is 2 hours; the ball milling speed of the second-level ball milling treatment is 1500 r / min, and the ball milling is 40 minutes.

[0109] The specific operation steps of the thermal efficiency improvement process of this embodiment are:

[0110] First, heat treat at 220°C for 40 min, then heat up to 420°C at a rate of 5°C / min and continue heat treatment for 20 min;

[0111] Finally, the temperature was raised to 530°C at a rate of 3°C / min, kept at this temperature for 1h, and finally air-cooled to room temperature;

[0112] The operation steps of the sintering improvement treatment are:

[0113] Heat treatment was performed at 760°C for 40 min, then the temperature was increased to 850°C at a rate of 3°C / min, kept at that temperature for 3 h, and finally air-cooled to room temperature.

[0114] The preparation method of the graphene modifying agent of this embodiment is:

[0115] S01: The graphene is first ultrasonically treated in a sufficient amount of hydrogen peroxide solution, with an ultrasonic power of 400W for 20 minutes. After the ultrasonic treatment is completed, the graphene is washed with water, filtered and dried;

[0116] S02: Preparation of modified solution doped with nano-titanium dioxide:

[0117] 3 parts of nano-silica sol and 4 parts of 5% by mass lanthanum chloride solution were added to 8 parts of sodium citrate solution, and then 4 parts of nano-titanium dioxide were added to fully blend to obtain a modified solution doped with nano-titanium dioxide;

[0118] S03: stirring and modifying the dried graphene and the modified solution doped with nano-titanium dioxide in a weight ratio of 3:7, and completing the modification to obtain a modified graphene agent;

[0119] S04: The modified graphene agent and the regulator are mixed in a weight ratio of 5:3 and ball-milled at a speed of 850 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain the graphene modified regulator.

[0120] The mass fraction of the hydrogen peroxide solution in this embodiment is 6%; the mass fraction of the sodium citrate solution is 7%; the stirring speed of the stirring modification treatment is 500 r / min, and the stirring time is 40 min.

[0121] The preparation method of the regulator of this embodiment is:

[0122] The nano-kaolin powder is first immersed in a zinc nitrate solution of 5 times the total amount of the nano-kaolin, and the solution is stirred sufficiently at a speed of 750 r / min for 2 hours. After the immersion is completed, the solution is filtered and dried to obtain a zinc-doped kaolin agent;

[0123] The flaky nano-alumina, chitosan solution and sodium dodecylbenzene sulfonate are mixed in a weight ratio of 3:5:1 to prepare a flaky nano-alumina liquid;

[0124] 7 parts of zinc-doped kaolin agent and 2 parts of silane coupling agent KH550 were added to 8 parts of flaky nano-alumina liquid, mixed and ball-milled for 2 hours at 750 r / min. After the ball-milling was completed, the regulator was filtered and dried.

[0125] The mass fraction of the zinc nitrate solution in this embodiment is 8%; the mass fraction of the chitosan solution is 5%.

[0126] The preparation method of the synergist of this embodiment is:

[0127] S11: irradiating the carbon nanotubes in a proton irradiation box at a power of 400 W for 30 minutes to obtain irradiated carbon nanotubes;

[0128] S12: 5 parts of 4% by mass sodium alginate solution, 3 parts of 5% by mass yttrium nitrate solution, 5 parts of hydroxyapatite and 2 parts of carboxymethyl cellulose are mixed to obtain a hydroxyapatite solution;

[0129] The irradiated carbon nanotubes and hydroxyapatite liquid were stirred and modified in a weight ratio of 2:5, with a stirring speed of 700 r / min for 30 minutes. After the stirring was completed, the mixture was washed with water, filtered and dried to obtain a synergist.

[0130] The lithium iron phosphate material is prepared by a method for preparing a lithium iron phosphate material in this embodiment.

[0131] The present embodiment provides an application of a lithium iron phosphate material in a positive electrode material of a lithium electronic battery.

[0132] Example 3

[0133] A method for preparing a lithium iron phosphate material according to the present embodiment comprises the following steps:

[0134] Step 1: Set the specific surface area to 6.5m / g iron phosphate and graphene modification agent are subjected to primary ball milling treatment in a weight ratio of 5:2.5, and after the ball milling is completed, the iron phosphate agent modified with graphene is obtained by suction filtration and drying;

[0135] Step 2: subjecting the graphene-modified iron phosphate agent to thermal efficiency improvement treatment, and after the treatment is completed, a thermally efficient iron phosphate body is obtained;

[0136] Step 3: The thermally effective iron phosphate, lithium carbonate and synergist are mixed in a weight ratio of 6:3.5:2 and subjected to secondary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain an improved lithium iron phosphate.

[0137] Step 4: The lithium iron phosphate improved body is sintered and improved, and the lithium iron phosphate material of the present invention is obtained after sintering.

[0138] The ball milling speed of the first-level ball milling treatment in this embodiment is 800 r / min, and the ball milling is 2 hours; the ball milling speed of the second-level ball milling treatment is 1250 r / min, and the ball milling is 35 minutes.

[0139] The specific operation steps of the thermal efficiency improvement process of this embodiment are:

[0140] First, heat treatment was performed at 215°C for 35 min, then the temperature was raised to 410°C at a rate of 3.5°C / min and heat treatment was continued for 20 min.

[0141] Finally, the temperature was raised to 515°C at a rate of 2°C / min, kept at this temperature for 1h, and finally air-cooled to room temperature;

[0142] The operation steps of the sintering improvement treatment are:

[0143] Heat treatment was performed at 755°C for 30-40 min, then the temperature was increased to 835°C at a rate of 2°C / min, kept at that temperature for 2.5 h, and finally air-cooled to room temperature.

[0144] The preparation method of the graphene modifying agent of this embodiment is:

[0145] S01: The graphene is first ultrasonically treated in a sufficient amount of hydrogen peroxide solution, with an ultrasonic power of 370W for 20 minutes. After the ultrasonic treatment is completed, the graphene is washed with water, filtered and dried;

[0146] S02: Preparation of modified solution doped with nano-titanium dioxide:

[0147] 2 parts of nano-silica sol and 3 parts of 5% by mass lanthanum chloride solution were added to 6.5 parts of sodium citrate solution, and then 3 parts of nano-titanium dioxide were added to fully blend to obtain a modified solution doped with nano-titanium dioxide;

[0148] S03: stirring and modifying the dried graphene and the modified solution doped with nano-titanium dioxide in a weight ratio of 3:7, and completing the modification to obtain a modified graphene agent;

[0149] S04: The modified graphene agent and the regulator are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 800 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain the graphene modified regulator.

[0150] The mass fraction of the hydrogen peroxide solution in this embodiment is 4.5%; the mass fraction of the sodium citrate solution is 5.5%; the stirring speed of the stirring modification treatment is 475 r / min, and the stirring time is 35 min.

[0151] The preparation method of the regulator of this embodiment is:

[0152] The nano-kaolin powder is first immersed in a zinc nitrate solution of 4 times the total amount of the nano-kaolin, and the solution is stirred sufficiently at a speed of 600 r / min for 2 hours. After the immersion is completed, the solution is filtered and dried to obtain a zinc-doped kaolin agent;

[0153] The flaky nano-alumina, chitosan solution and sodium dodecylbenzene sulfonate are mixed in a weight ratio of 3:5:1 to prepare a flaky nano-alumina liquid;

[0154] 5.5 parts of zinc-doped kaolin agent and 1.5 parts of silane coupling agent KH550 were added to 6.5 parts of flaky nano-alumina liquid, mixed and ball-milled for 2 hours at 600 r / min. After the ball-milling was completed, the regulator was filtered and dried.

[0155] The mass fraction of the zinc nitrate solution in this embodiment is 6%; the mass fraction of the chitosan solution is 4%.

[0156] The preparation method of the synergist of this embodiment is:

[0157] S11: irradiating the carbon nanotubes in a proton irradiation box at a power of 370 W for 25 min to obtain irradiated carbon nanotubes;

[0158] S12: 3.5 parts of 4% sodium alginate solution, 2 parts of 5% yttrium nitrate solution, 4 parts of hydroxyapatite and 1.5 parts of carboxymethyl cellulose are mixed to obtain a hydroxyapatite solution;

[0159] The irradiated carbon nanotubes and hydroxyapatite liquid were stirred and modified in a weight ratio of 2:5, with a stirring speed of 670 r / min for 25 minutes. After the stirring was completed, the mixture was washed with water, filtered and dried to obtain a synergist.

[0160] The lithium iron phosphate material is prepared by a method for preparing a lithium iron phosphate material in this embodiment.

[0161] The present embodiment provides an application of a lithium iron phosphate material in a positive electrode material of a lithium electronic battery.

[0162] Comparative Example 1

[0163] The difference from Example 3 is that no graphene modification treatment is used.

[0164] Comparative Example 2

[0165] The difference from Example 3 is that the graphene modifying agent is not treated with a modifying liquid doped with nano-titanium dioxide.

[0166] Comparative Example 3

[0167] The difference from Example 3 is that nano titanium dioxide and nano silica sol are not added to the modified solution doped with nano titanium dioxide.

[0168] Comparative Example 4

[0169] The difference from Example 3 is that no lanthanum chloride solution is added to the modified solution doped with nano-titanium dioxide, and water is used instead of the sodium citrate solution.

[0170] Comparative Example 5

[0171] The difference from Example 3 is that no conditioning agent treatment was used.

[0172] Comparative Example 6

[0173] The difference from Example 3 is that no synergist was added.

[0174] Comparative Example 7

[0175] The difference from Example 3 is that no irradiated carbon nanotubes are added to the synergist.

[0176] Comparative Example 8

[0177] The difference from Example 3 is that hydroxyapatite liquid treatment is not used in the preparation of the enhancer.

[0178] Comparative Example 9

[0179] The difference from Example 3 is that hydroxyapatite and carboxymethyl cellulose are not added to the hydroxyapatite liquid.

[0180] Comparative Example 10

[0181] The difference from Example 3 is that no yttrium nitrate solution is added to the hydroxyapatite solution, and deionized water is used instead of the sodium alginate solution.

[0182] The products of Examples 1 to 3 and Comparative Examples 1 to 10 were subjected to performance tests, and the test results are as follows:

[0183] The present invention also conducts a high temperature stability test based on the specific capacity test after 1000 cycles at 10C rate, and the test is as follows:

[0184]

[0185] It can be seen from the comparative examples 1-10 and the examples 1-3 and the tests under high temperature conditions;

[0186] The product of Example 3 has conductivity and specific capacity after 1000 cycles at 10C rate, and the two performances can achieve coordinated improvement, and the product has significant stability effect on specific capacity performance after cycling under high temperature conditions;

[0187] It can be seen from Comparative Example 1, Comparative Example 6 and Example 3 that the present invention does not use one of the graphene modification agent treatment and the synergist addition, and the performance stability of the product shows a significant trend of deterioration. The two are coordinated and synergistic, and the performance effect of the product is most significant;

[0188] As can be seen from Comparative Examples 2-5 and Example 3, the graphene modifying agent was not treated with a modifying liquid doped with nano-titanium dioxide, nano-titanium dioxide and nano-silica sol were not added to the modifying liquid doped with nano-titanium dioxide, lanthanum chloride solution was not added to the modifying liquid doped with nano-titanium dioxide, and sodium citrate solution was replaced with water, and no conditioning agent was used. The performance of the product has a trend of varying degrees of deterioration. At the same time, the performance of the product has a large trend of deterioration without the conditioning agent. The graphene modifying agent obtained by treating the modifying liquid doped with nano-titanium dioxide obtained by the specific method of the present invention with the conditioning agent has the most significant performance effect. The graphene modifying agents obtained by replacing with other methods are not as obvious as the effect of the present invention.

[0189] It can be seen from Comparative Examples 7-10 and Example 3 that the performance of the products tends to deteriorate when no irradiated carbon nanotubes are added to the enhancer, no hydroxyapatite liquid treatment is used in the preparation of the enhancer, no hydroxyapatite and carboxymethyl cellulose are added to the hydroxyapatite liquid, no yttrium nitrate solution is added to the hydroxyapatite liquid, and deionized water is used instead of sodium alginate solution. The performance effect of the product is most significant when the hydroxyapatite liquid obtained by the specific method of the present invention is combined with irradiated carbon nanotubes.

[0190] The present invention further explores the product performance through the regulator;

[0191] Experimental Example 1

[0192] The only difference from Example 3 is that no zinc-doped kaolin agent is added to the regulator.

[0193] Experimental Example 2

[0194] The only difference from Example 3 is that the zinc-doped kaolin agent is replaced by kaolin raw material.

[0195] Experimental Example 3

[0196] The only difference from Example 3 is that no flake nano alumina liquid is added to the regulator. The specific preparation method is:

[0197] The nano-kaolin powder is first immersed in a 6% zinc nitrate solution with a mass fraction of 4 times the total amount of the nano-kaolin, and the solution is stirred sufficiently at a speed of 600 r / min for 2 hours to obtain a zinc-doped kaolin agent;

[0198] 5.5 parts of zinc-doped kaolin agent and 1.5 parts of silane coupling agent KH550 were mixed and ball-milled for 2 hours at 600 r / min. After the ball-milling was completed, the regulator was filtered and dried.

[0199] Experimental Example 4

[0200] The only difference from Example 3 is that no flake nano alumina is added to the flake nano alumina liquid.

[0201] Experimental Example 5

[0202] The only difference from Example 3 is the preparation method of the regulator, which is as follows:

[0203] The preparation method of the regulator is:

[0204] The nano-kaolin powder is first immersed in a 6% zinc nitrate solution with a mass fraction of 4 times the total amount of the nano-kaolin, and the mixture is immersed and stirred sufficiently at a speed of 600 r / min for 2 hours. After the immersion is completed, the mixture is filtered and dried to obtain a zinc-doped kaolin agent;

[0205] The flaky nano-alumina, water and sodium dodecylbenzene sulfonate are mixed in a weight ratio of 3:5:1 to prepare a flaky nano-alumina liquid;

[0206] Add 5.5 parts of zinc-doped kaolin agent into 6.5 parts of flaky nano-alumina liquid, mix and ball-mill for 2 hours at 600 r / min. After the ball-milling is completed, filter and dry to obtain a regulator.

[0207] The present invention is based on the test under high temperature resistance conditions, and the performance tests of the products of Experimental Examples 1-5 are as follows:

[0208]

[0209] It can be seen from Experimental Examples 1-5 that when no zinc-doped kaolin agent is added to the regulator, the performance of the product changes. Among the factors in the preparation of the regulator, the performance deterioration is the most obvious, followed by the fact that no flaky nano-alumina liquid is added. At the same time, when the zinc-doped kaolin agent is replaced by kaolin raw material, no flaky nano-alumina is added to the flaky nano-alumina liquid, and the preparation methods of the regulator are different, the performance of the product has a tendency to deteriorate to varying degrees. When the preparation raw materials and preparation process in the preparation of the regulator are changed, the performance of the product has a tendency to deteriorate. The preparation using other methods to replace the regulator is not as significant as the effect of the present invention.

[0210] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0211] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a lithium iron phosphate material, characterized in that: The following steps are involved: Step 1: Set the specific surface area to 5-8m 2 / g iron phosphate and graphene modification agent are subjected to primary ball milling treatment in a weight ratio of 5:(2-3), and after the ball milling is completed, the iron phosphate agent modified with graphene is obtained by suction filtration and drying; Step 2: subjecting the graphene-modified iron phosphate agent to thermal efficiency improvement treatment, and after the treatment is completed, a thermally efficient iron phosphate body is obtained; Step 3: Mix the thermally effective iron phosphate, lithium carbonate and synergist in a weight ratio of (5-7): (3-4): 2 and perform a secondary ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain an improved lithium iron phosphate. Step 4: The lithium iron phosphate improved body is sintered and improved, and the lithium iron phosphate material is obtained after sintering; The specific operation steps of the thermal efficiency improvement treatment are: First, heat treat at 210-220℃ for 30-40min, then heat up to 400-420℃ at a rate of 2-5℃ / min, and continue heat treatment for 20min; Finally, heat to 500-530℃ at a rate of 1-3℃ / min, keep warm for 1h, and finally air cool to room temperature; The operation steps of the sintering improvement treatment are: Heat treatment at 750-760℃ for 30-40min, then heat to 820-850℃ at a rate of 1-3℃ / min, keep at this temperature for 2-3h, and finally air cool to room temperature; The preparation method of the graphene modifying agent is: S01: The graphene is first ultrasonically treated in a sufficient amount of hydrogen peroxide solution, with an ultrasonic power of 350-400W for 20 minutes. After the ultrasonic treatment is completed, the graphene is washed with water, filtered and dried; S02: Preparation of modified solution doped with nano-titanium dioxide: 1-3 parts of nano-silica sol and 2-4 parts of 5% by mass lanthanum chloride solution are added to 5-8 parts of sodium citrate solution, and then 2-4 parts of nano-titanium dioxide are added to fully blend to obtain a modified solution doped with nano-titanium dioxide; S03: stirring and modifying the dried graphene and the modified solution doped with nano-titanium dioxide in a weight ratio of 3:7, and completing the modification to obtain a modified graphene agent; S04: The modified graphene agent and the regulator are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 750-850 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a graphene modified regulator; The preparation method of the regulator is: The nano-kaolin powder is first immersed in a zinc nitrate solution 3-5 times the total amount of the nano-kaolin and stirred sufficiently, the immersion speed is 550-750r / min, the immersion is carried out for 2h, and after the immersion is completed, the kaolin agent doped with zinc is obtained by suction filtration and drying; The flaky nano-alumina, chitosan solution and sodium dodecylbenzene sulfonate are mixed in a weight ratio of 3:5:1 to prepare a flaky nano-alumina liquid; Add 4-7 parts of zinc-doped kaolin agent and 1-2 parts of silane coupling agent KH550 to 5-8 parts of flaky nano-alumina liquid, mix and ball-mill for 2 hours at 550-750r / min. After the ball-milling is completed, filter and dry to obtain a regulator; The preparation method of the synergist is: S11: irradiating the carbon nanotubes in a proton irradiation box at a power of 350-400 W for 20-30 min to obtain irradiated carbon nanotubes; S12: 2-5 parts by mass of 4% sodium alginate solution, 1-3 parts by mass of 5% yttrium nitrate solution, 3-5 parts by mass of hydroxyapatite and 1-2 parts by mass of carboxymethyl cellulose are mixed to obtain a hydroxyapatite solution; The irradiated carbon nanotubes and hydroxyapatite liquid are stirred and modified in a weight ratio of 2:5, with a stirring speed of 650-700 r / min for 20-30 minutes. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a synergist.

2. The method for preparing a lithium iron phosphate material according to claim 1, characterized in that: The ball milling speed of the first-level ball milling treatment is 750-850 r / min, and the ball milling is 2 hours; the ball milling speed of the second-level ball milling treatment is 1000-1500 r / min, and the ball milling is 30-40 minutes.

3. The method for preparing a lithium iron phosphate material according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide solution is 3-6%; the mass fraction of the sodium citrate solution is 4-7%; the stirring speed of the stirring modification treatment is 450-500r / min, and the stirring time is 30-40min.

4. The method for preparing a lithium iron phosphate material according to claim 3, characterized in that: The mass fraction of the zinc nitrate solution is 4-8%; the mass fraction of the chitosan solution is 3-5%.

5. The lithium iron phosphate material prepared by the method for preparing a lithium iron phosphate material according to any one of claims 1 to 4.

6. Use of the lithium iron phosphate material as claimed in claim 5 in positive electrode materials for lithium electronic batteries.

Citation Information

Patent Citations

  • Graphene / titanium dioxide / lithium ion phosphate aerogel battery anode material and preparation method thereof

    CN108232180A

  • Method for preparing lithium iron phosphate positive electrode material from iron phosphate

    CN116632232A